Attenuating Effect of Spirulina (Arthrospira platensis) against Di (2-ethylhexyl) Phthalate Induced Toxicity in Wistar Rat. Issue 1 (31st December 2023) - Rashed Alqahtani, Munira Abdullah; Virk, Promy; Fouad, Dalia
ABSTRACT: Di(2-ethylhexyl) phthalate (DEHP) is an extensively used plasticizer and being non-covalently bound to plastics it leaches out into the environment. This addresses a grave concern on its potential human exposure and subsequent deleterious effects. The ameliorative potential of Spirulina (Arthrospira platensis) against DEHP-induced toxicity was assessed in rats. Group I was control. Group II and III, were exposed to a low dose of DEHP (125 mg/kg), and Group IV and V were exposed to a high dose of DEHP (250 mg/kg). Group III and V were treated with spirulina orally (1000 mg/Kg) for 3 weeks. Exposure to DEHP elicited marked oxidative stress and associated DNA damage in a dose-dependent manner. The hepatic expression of p53 was also significantly suppressed. Liver and kidney function tests showed marked alterations. Treatment with spirulina efficaciously reversed the adverse effects. Thus, these findings offer a nutritional intervention of spirulina to combat the environmental exposure to plasticizers. GRAPHICAL ABSTRACT: uf0001